Students’ expectations and perceptions on service quality of e-learning in a selected faculty of a public university in Malaysia - Li, Chen Yan; Asimiran, Soaib; Suyitno (Atlantis Press, 2018)
The main purpose of this quantitative research is to examine students’ expectations and perceptions on the service quality of e-learning in a selected faculty of a public university in Malaysia. Data for the research are collected through a survey on sixth semester undergraduate students in one of the faculties in a public university. Questionnaire is adopted based on Parasuraman’s (1994) SERVQUAL model which includes five dimensions: reliability, responsiveness, empathy, tangibility and assurance. Descriptive analysis is conducted to indicate the level of students’ expectations and perceptions on service quality of e-learning as well as the gap between their expectations and perceptions. Paired t-test analysis is performed to test the significant difference between students’ expectations and perceptions. The findings indicate that the level of students’ expectations is high with tangibility regarded as the highest amongst the five domains examined. However, the level of students’ perceptions is medium. Among the five dimensions, the level of perception towards assurance is the highest, while the level of perception towards empathy is the lowest. There exists a gap between students’ expectations and students’ perceptions. Paired ttest shows that there is a significant difference between students’ expectations and perceptions indicating students are not highly satisfied with the service quality of e-earning provided by the selected university. Further initiatives should be taken by the university to improve the service quality of the e-learning facilities focusing on areas identified in the findings.